Emaranhamento e discórdia em sistemas puros multipartidos - Ferreira, Jonhy Syllas dos Santos (2015)
In bipartite systems, it is known that entanglement formation and quantum discord are different for mixed states. There is no clear relations between them apparently. However, when considering pure three-partite systems, have the conservation law which establishe a distribution of entanglement and discord through the subsystems. The sum of entanglements of a particular subsystem with the other ones is equal to the sum of discords betweell the same subsystems. Therefore, the bipartite entanglements can not be increased without increasing by the same amount the sum of discords. In this work, we derive relations between entanglement and discord for systems of 4, 5 and 6 parts. Notably, the relation between the entanglement and discord for even and odd number of systems are different. For even number of parts, relationships are inequalities, while for the odd number of parts, they are equalities, for which demonstrate its generalization. We also use the relation between thermodynamic work and discord to relate the sum of entanglements of formation with the difference in the performance of between quantum and classical Maxwell's Demon.